INOVASI WEDANG MOCHI SEBAGAI ALTERNATIF MINUMAN TRADISIONAL - Khairunnisa Alya Yumna Oci (LPSDI Bina Patria, 2024)
In today's modern era, local wisdom needs to be preserved. Thus, the product innovation “Wedang Mochi” was made. Wedang jahe is often served hot or warm. Not only as a traditional drink, and cultural heritage, wedang jahe also has many health benefits. While mochi is made from tapioca flour or glutinous rice flour and then compacted into an elastic dough. This product innovation is expected to increase awareness of wedang jahe by attracting the attention of various groups of people who dislike wedang jahe. Experimental research on mochi products involved the use of rice flour-based skin. This research aims at people who want product innovations that are safe for consumption. The results of the organoleptic test to determine a good recipe formula and public acceptability using the questionnaire distribution method. Based on the results to determine public acceptance, it shows that wedang mochi is acceptable and liked by the public.